How Students Solve The Logarithm? Conceptual and Procedural Understanding - Kusuma, Heri; masduki, masduki (Journal of Research and Advances in Mathematics Education, 2016)
The purpose of this study was to describe the understanding of tenth grade students in logarithms. The descriptive qualitative research was conducted with three students as participants representing the high, medium, and low category. The data was collected by performing observation, tests, interviews, and documentation. They were analyzed by data reduction, data display, and conclusion. The results of this study indicates that students with high category tended to have a good understanding on both conceptual and procedural category. Students with medium category have a good procedural understanding nevertheless weak on the conceptual. Finally, The students with low category had weak ability understanding on both conceptual and procedural. Thus, it can be concluded that the studentâs understanding influence their abilities in solving mathematics problems.